Integrating an LFA Carbapenemase Detection System into the Laboratory Diagnostic Routine: Preliminary Data and Effectiveness Against Enzyme Variants - Maddalena Calvo; Gaetano Maugeri; Dafne Bongiorno; Giuseppe Migliorisi; Stefania Stefani (Diagnostics)
Background/Objectives. Carbapenemase production is the most diffused carbapenem-resistance mechanism among Enterobacterales, with Klebsiella pneumoniae carbapenemase (KPC), Verona-imipenemase (VIM), New-Delhi metallo-β-lactamase (NDM), imipenemase (IMP), and oxacillinase (OXA-48) being reported as the main types within Europe. Particularly, Southern Italy holds a concerningly high percentage of carbapenemases-producing Enterobacterales diffused among different hospital settings. These strains may colonize critical patients’ gastrointestinal tracts, often causing disseminations and severe complications. Scientific data recently reported carbapenemase variants’ worldwide diffusion and several double-carbapenemases reports. The diagnostic routine needs devices whose detection rates are extended to similar epidemiological conditions, avoiding a lack of specificity and potential negative results. Methods. We planned a retrospective study including carbapenem- and/or ceftazidime/avibactam-resistant Enterobacterales (62) which were tested with the KPC/IMP/NDM/VIM/OXA-48 Combo Test Kit (KINVO, Medomics Medical Technology, Nanjing, Jiangsu, China) based on the lateral flow assay (LFA) method. Results. We compared its results to the phenotypic antimicrobial susceptibility testing (AST) MIC results, obtaining a 100% agreement rate. The LFA kit reported carbapenemases in all the tested strains, also identifying cases of KPC variants and double-carbapenemases production. Conclusions. Our data demonstrated how LFAs may represent a reliable alternative requiring minimum economic and personnel resources along with simple result interpretations. Future studies will be necessary to further investigate the system effectiveness on a larger isolates’ number and a broad carbapenemase variant spectrum.